Kohautia nagporensis (Brace Ex Haines) Sant. et Merch.-an Imperfectly Known Species from Upper Gangetic Plain - Sharma, V. S. (Indian Forester, 1973)
The paper records for the first time the occurrence of a very rare plant-Kohautia nagporensis (Brace ex Haines) Sant.&Merch., from the region of Upper Gangetic Plain. It further deals with the nomenclatural history, synonymy, description, and the known distribution of the species, which Is hitherto lacking in botanical literature and is more or less, in a state of confusion as regards its botanical identity. Also, for the first time, ample material of the above rare species was gathered by the author from Ajmer (Rajasthan) and consequently, a detailed description of the taxon is provided.